2008
DOI: 10.1542/peds.2007-2290
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rotavirus Antigenemia and Extraintestinal Manifestations in Children With Rotavirus Gastroenteritis

Abstract: Rotavirus antigenemia is frequently observed in a patient's serum during the acute phase, and viral antigen levels change dramatically during the acute phase of the illness. Because patients with fever had higher rotavirus antigen levels, antigenemia severity might contribute to fever. The host immune response plays an important role in controlling antigenemia levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 24 publications
7
73
2
5
Order By: Relevance
“…15 Therefore, systemic manifestations including cutaneous disorders, although rare, may be associated with rotavirus infection. 16 Ruzicka et al, 12 reported the first case of a patient with signs of hepatitis and generalized maculo-papular exanthema which developed one week after his two sons had suffered from rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Therefore, systemic manifestations including cutaneous disorders, although rare, may be associated with rotavirus infection. 16 Ruzicka et al, 12 reported the first case of a patient with signs of hepatitis and generalized maculo-papular exanthema which developed one week after his two sons had suffered from rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the overall picture that emerges from our findings is that polymorphisms in genes involved in polysaccharide recognition, signal transduction, inhibition of T-cell proliferation, pro-inflammatory signaling and eventual production of antimicrobial peptides are associated with antibody response to the Vi polysaccharide vaccine for typhoid. However, just as co-infection with parasites (Harris et al 2009) or other infectious agents (Sugata et al 2008;Lin et al 2006) can influence immunological response to a pathogen, it is possible, that antibody response to vaccination with Vi polysaccharide may be affected by coinfections or prior exposure. While it is difficult to rule out the involvement of other genes in modulation of immune response to the Vi polysaccharide vaccine, the 7 genes that we have found to be associated with host antibody response to the polysaccharide vaccine provide a foundation for elucidating the functional mechanism of the products of these genes in host response to the polysaccharide vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…in that 756 (76.6%) of 987 rotavirus infected patients were classified in the severe state 13) . They also reported that the body temperature and serum levels of rotavirus antigen were higher in the severe state.…”
Section: ㆍ대한소아소화기영양학회지:제 14 권 제 2 호 2011mentioning
confidence: 98%